Behavior of overhead transmission line parameters on the presence of ground-wires - Kurokawa, S.; Pissolato, J.; Tavares, M. C.; Portela, C. M.; Prado, A. J. (Institute of Electrical and Electronics Engineers (IEEE), 2005)
Initially this paper shows the ground wire reduction process for generic multiphase transmission lines and after, the ground wire reduction process for a specilic 440-kV three-phase overhead transmission line. Following this, the influence of the ground wire reduction process considering two situations is shown: first, considering frequency independence and second, when these parameters are considered as frequency dependent. This paper presents analytical results for generic multiphase transmission lines. For a specific 440-kV three-phase overhead transmission line, analytical and graphic results are shown considering real data for every frequency between 10 Hz and 1 MHz.
Keywords: admittance matrix; electromagnetic (EM) field; frequency-domain analysis; impedance matrix; multiconductor transmission lines; transmission-line matrix methods; transmission-line theory